Pendidikan Kesehatan dan Peningkatan Pengetahuan Dan Kemampuan Petugas Kesehatan dan Kader dalam Melaksanakan Posyandu System 5 Meja - Idris, Idris; Nursiah, Andi; Mildaratu, Mildaratu; Wahyuni, Sri; P, Nur Triningtias; Aripa, Lusyana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Health services are any efforts carried out individually or collectively within an organization to maintain and improve health, prevent and cure disease, and restore the health of individuals, families, groups and/or communities. The aim of this service activity is to increase the knowledge and ability of cadres to implement the 5 table posyandu system. Cadre training related to the implementation of posyandu 11 people. The method is carried out using Health Education, Increasing Knowledge and Assistance in the implementation of posyandu. The result of this activity is that there is still a need for follow-up cadre meetings to evaluate the implementation of Posyandu, follow-up on measuring the weighing of toddlers with home visits and follow-up on future implementation. The conclusion is that the discipline of the cadres and toddlers really determines the success of the implementation of the posyandu so that monitoring of the growth and development of toddlers continues to be carried out according to the program that has been prepared.